2016
DOI: 10.1371/journal.pone.0163568
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Sodium/Hydrogen Exchanger NHA2 Exacerbates Obesity- and Aging-Induced Glucose Intolerance in Mice

Abstract: We previously demonstrated that the sodium/hydrogen exchanger NHA2, also known as NHEDC2 or SLC9B2, is critical for insulin secretion by β–cells. To gain more insights into the role of NHA2 on systemic glucose homeostasis, we studied the impact of loss of NHA2 during the physiological aging process and in the setting of diet-induced obesity. While glucose tolerance was normal at 2 months of age, NHA2 KO mice displayed a significant glucose intolerance at 5 and 12 months of age, respectively. An obesogenic high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…SLC activity is a highly heritable trait, associated with abnormalities in Na + homeostasis, diabetes mellitus and arterial hypertension in humans [4][5][6][7][8][9] . We previously demonstrated that NHA2 resides in endosomes of β-cells and is critical for insulin secretion 10,11 . In support of this finding, a single-nucleotide polymorphism in the NHA2 gene was recently discovered in a genome-wide association study as a new locus associated with type 2 diabetes in humans 12 .…”
Section: Translational Stateentmentioning
confidence: 99%
See 1 more Smart Citation
“…SLC activity is a highly heritable trait, associated with abnormalities in Na + homeostasis, diabetes mellitus and arterial hypertension in humans [4][5][6][7][8][9] . We previously demonstrated that NHA2 resides in endosomes of β-cells and is critical for insulin secretion 10,11 . In support of this finding, a single-nucleotide polymorphism in the NHA2 gene was recently discovered in a genome-wide association study as a new locus associated with type 2 diabetes in humans 12 .…”
Section: Translational Stateentmentioning
confidence: 99%
“…We previously demonstrated that NHA2 plays an important role in secretagogue-mediated insulin secretion in pancreatic β-cells 10,11 . Three months old NHA2 KO mice fed a regular chow, as employed in the current study, have similar blood glucose and insulin levels in fasting and fed state compared to WT mice 10,11 . In a next step, we studied the impact of NHA2 depletion on a cellular level in vitro, using mpkDCT 4 cells, a well-characterized murine DCT cell line that expresses NCC (Suppl.…”
Section: Nha2 Regulates Wnk-ncc Axis In a Cell Autonomous Mannermentioning
confidence: 99%
“…The SLC9 gene family encodes Na + /H + exchangers (NHEs), which are fatal for transepithelial movement of Na + and HCO 3− in the kidney (Fuster and Alexander 2014). Another study found that the distribution and expression of NHA2 are especially limited to individual organs, such as in the bone or distal tubules of the kidney (Deisl et al 2016). NHA2 resides in the plasma membrane of Madin–Darby canine kidney (MDCK) cells, which are highly enriched and functionally significant in renal tubules (Chintapalli et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The functions of the SLC9B and SLC9C isoforms are less well characterized. SLC9B isoforms are broadly expressed and have been implicated in hypertension ( Xiang et al, 2007 ; Chintapalli et al, 2015 ; Kondapalli et al, 2017 ), insulin secretion ( Deisl et al, 2013 ; Deisl et al, 2016 ) and sperm motility and fertility ( Chen et al, 2016 ). By contrast, expression of the SLC9C isoforms is largely confined to testis where they are also essential for sperm function ( Wang et al, 2003 ; Quill et al, 2006 ; Wang et al, 2007 ; Windler et al, 2018 ; Cavarocchi et al, 2021 ).…”
Section: The Nhe Familymentioning
confidence: 99%